Joseph Życiński’s struggle with the language about God - Heller, Michał (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
In the two-volume work Theism and the Analytical Philosophy (1985; 1988a) Joseph Życiński took up the challenge of renewing Christian metaphysics so that it could appear as a full-fledged partner in the dialogue with other streams of contemporary philosophy. This renewal should use two sources: the methodological principles of analytic philosophy, especially its philosophy of language, and certain elements of Whitehead’s process philosophy. This study presents a critical reconstruction of Życiński’s arguments contained in the first two chapters of (1985), which are devoted to the problem of language. Main results of this part of Życiński’s work are negative, that is, they refute the arguments and interpretations of those analytical philosophers who show the meaninglessness of the theistic language or try to assimilate it to other standard languages, depriving it of a reference to the transcendent reality. How can a positive part of the Życiński program be developed? It seems that only by formulating specific problems in the field of philosophy of God, or even theology, and choosing the right linguistic tools to drill down on a given problem and seek its solution. This is in line with Wittgenstein’s concept of language games. Życiński tries to do this in (1988a). Życiński turned out to be a precursor of nowadays increasingly developing analytical theology.